DEVELOPMENT OF A TWO-TIER MULTIPLE-CHOICE DIAGNOSTIC TEST TO IDENTIFY STUDENTS’ MISCONCEPTIONS IN CHEMISTRY USING THE RASCH MODEL - Supardi, Rafsanjani; Hasim, Muhammad; Setialaksana, Wirawan; Syam, Sriwidayani; Anwar, Andi Ratu Ayu Ashari (Lembaga Penelitian Mahasiswa Penalaran UNM, 2025)
This study is designed to develop a two-tier multiple-choice diagnostic assessment tool to identify students' misconceptions in chemistry, particularly on the topics of conductive and non-conductive solutions, as well as reduction and oxidation processes. The development method follows the adapted framework of Wilson, Orindo, and Antonio, streamlined into three core phases: planning, feasibility assessment, and field testing. Validation was conducted through expert evaluation and the application of Rasch statistical analysis. The assessment tool demonstrated excellent content quality, with an Aiken score of 0.86, confirming its alignment with learning materials and the objective of enhancing students' analytical skills. Field testing confirmed that the tool meets all Rasch measurement criteria, including unidimensionality, answer independence, parameter consistency, model fit, and item difficulty variation. The tool also exhibited strong measurement consistency, performing optimally in assessing students with intermediate ability levels. Thus, this instrument is deemed suitable for identifying conceptual errors in chemistry learning and serves as a guide for formulating effective instructional strategies.